1986
DOI: 10.1002/dc.2840020112
|View full text |Cite
|
Sign up to set email alerts
|

Chordoma: Cytologic and immunocytochemical study of four cases

Abstract: We present the cytologic features and the immunocytochemical profile of four cases of chordoma on fine-needle aspiration biopsies. The physaliferous cells in signet-ring, pearl-like formations and the trabecular arrangement with rounded contours are distinctive. Other cell types and cellular arrangements are also described. The negative immunoreactivity of carcinoembryonic antigen (CEA) and the positive staining pattern for neuron-specific enolase (NSE), S-100 protein, epithelial membrane antigen (EMA), and ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 10 publications
4
47
0
Order By: Relevance
“…The cytologic features of this case were not different from those previously reported. 2,3,[5][6][7][8][10][11][12][13][14]16 However, physaliferous cells, which are important to the histologic diagnosis as well as aspiration cytology of chordoma, were scarcely observed in the present cytologic specimens, and none were observed in the sputum. to be essential to FNAC since a lack of vacuolated tumor cells has been reported in one case of chordoma, even in the primary tumor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cytologic features of this case were not different from those previously reported. 2,3,[5][6][7][8][10][11][12][13][14]16 However, physaliferous cells, which are important to the histologic diagnosis as well as aspiration cytology of chordoma, were scarcely observed in the present cytologic specimens, and none were observed in the sputum. to be essential to FNAC since a lack of vacuolated tumor cells has been reported in one case of chordoma, even in the primary tumor.…”
Section: Discussionmentioning
confidence: 99%
“…4 Immunohistochemistry is another help in differentiating chordoma from chondrosarcoma or adenocarcinoma. Previous immunohistochemical studies 5,6,8 have shown that chordoma is S-100 protein and EMA positive. EMA is negative in chondrosarcoma cells although positive in carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunohistochemical methods show regular S-100 and cytokeratin positivity with unequal epithelial membrane antigen staining in a very different pattern from the one in our case. 13,14,20,25,29 Another, recently described glial chordoid tumor appears in women near the third ventricle 3,13,27 and had a possible ependymal origin. 5,24 An epithelioid pattern with regular, oval nuclei in a mucofibrillar background has been described.…”
Section: Discussionmentioning
confidence: 99%
“…1,[3][4][5][6][7][8][9] The classic cytologic features of chordoma, such as physaliferous cells, small epithelioid cells and a myxoid background, have been described. 4,5,7,[10][11][12][13][14][15][16][17][18] However, physaliferous cells, considered a diagnostic histologic feature, are not consistently observed in smears, making the diagnosis difficult for the inexperienced cytopathologist. 5,8,[19][20][21] Our study was undertaken to review the clinical and cytomorphologic features of chordomas diagnosed by the use of FNAB at our institution.…”
Section: Clinical Datamentioning
confidence: 99%